2023
DOI: 10.11646/zootaxa.5306.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphometric analyses reveal host-specific cryptic speciation in a mite species, Tetranychus neocaledonicus (Andre, 1933) (Acari: Tetranychidae)

R. MEGHANA,
P. P. ANAND,
Y. SHIBU VARDHANAN

Abstract: Host- and habitat-induced morphological shape and size variations are common in phytophagous and parasitic taxa. Several integrated morphological and molecular techniques have been commonly used to understand host-induced morpho-cryptic species forms. Compared to other arthropods, cryptic speciation was more common in Acari. This study focused on the host-specific morphological cryptic shape and size variations of Tetranychus neocaledonicus, collected from moringa and cassava hosts. We used geometric morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 120 publications
0
0
0
Order By: Relevance
“…However, a recent study, based on sequence data and morphology, suggested it to be an endemic species with a vulnerable conservation ranking ( Shepherd et al 2023 ). Thus, integrating research results from morphological classification, molecular systematics, ecology and other fields, holds significant guiding significance for the rapid and accurate identification of cryptic species ( Kabus et al 2023 ; Meghana et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study, based on sequence data and morphology, suggested it to be an endemic species with a vulnerable conservation ranking ( Shepherd et al 2023 ). Thus, integrating research results from morphological classification, molecular systematics, ecology and other fields, holds significant guiding significance for the rapid and accurate identification of cryptic species ( Kabus et al 2023 ; Meghana et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%